Stock status of kawakawa Euthynnus affinis (Cantor, 1849) fishery using surplus production model: An assessment from coastal waters of Tamil Nadu, Bay of Bengal, Southeast coast of India - Rajendran Abinaya; Moosambikandy K. Sajeevan (Aquaculture and Fisheries)
Kawakawa Euthynnus affinis (Cantor, 1849) is one of the commercially exploited tuna fishery resource of India. Except landing data, no other information was available on its stock status. Hence, present study investigated the sustainability status of kawakawa fishery from Tamil Nadu, India. Data on annual catch and effort were reconstructed for the period of 2001–2020. The Catch-based MSY (CMSY), the Bayesian state-space Schaefer surplus production Model (BSM), and stochastic Surplus Production model in Continuous Time (SPiCT) packages were used to investigate the stock exploitation by running surplus production models with catch, catch per unit effort (CPUE), and other life history data. The biological reference points result of maximum sustainable yield (MSY) or biomass giving MSY (Bmsy) and fishing mortality giving MSY (Fmsy) of all the models indicated that the kawakawa stock in Tamil Nadu was subjected to overfishing and heading towards overfished status in recent decades. Results of the present study suggest reduction of fishing effort to keep the landing at MSY level and achieve a sustainable fishery.